Translating ethnographic data into knowledge, skills, and attitude statements for medical scribes: a modified Delphi approach. (11th June 2022) - Corby, Sky; Ash, Joan S; Whittaker, Keaton; Mohan, Vishnu; Solberg, Nicholas; Becton, James; Bergstrom, Robby; Orwoll, Benjamin; Hoekstra, Christopher; Gold, Jeffrey A
Abstract: Objective: While the use of medical scribes is rapidly increasing, there are not widely accepted standards for their training and duties. Because they use electronic health record systems to support providers, inadequately trained scribes can increase patient safety related risks. This paper describes the development of desired core knowledge, skills, and attitudes (KSAs) for scribes that provide the curricular framework for standardized scribe training. Materials and Methods: A research team used a sequential mixed qualitative methods approach. First, a rapid ethnographic study of scribe activities was performed at 5 varied health care organizations in the United States to gather qualitative data about knowledge, skills, and attitudes. The team's analysis generated preliminary KSA related themes, which were further refined during a consensus conference of subject-matter experts. This was followed by a modified Delphi study to finalize the KSA lists. Results: The team identified 90 descriptions of scribe-related KSAs and subsequently refined, categorized, and prioritized them for training development purposes. Three lists were ultimately defined as: (1) Hands-On Learning KSA list with 47 items amenable to simulation training, (2) Didactic KSA list consisting of 32 items appropriate for didactic lecture teaching, and (3) Prerequisite KSA list consisting of 11 items centered around items scribes should learn prior to being hired or soon after being hired. Conclusion: We utilized a sequential mixed qualitative methodology to successfully develop lists of core medical scribe KSAs, which can be incorporated into scribe training programs.